Respostas fisiológicas, bioquímicas e fitoquímicas de Ocimum gratissimum após a elicitação - Alvarenga, Joyce Pereira (2018)
The species Ocimum gratissimum L. (Lamiaceae) is widely known in several regions of the world, due to its condiment, culinary and medicinal properties. In addition, the essential oil of this species has antifungal and antioxidant activity, allowing its commercial application. However, there is an issue with the production of these essential oils, their synthesis occurs with a low yield. For this reason, studies have used elicitors to solve this obstacle. The elicitors are natural or synthetic compounds that act mimicking the effects of stress on plants, thus promoting the elicitation of defense responses. The phytohormone salicylic acid, which is already related to the process of systemic resistance in plants, has been used as an elicitor to optimize the production of secondary metabolites. Another problem related to essential oils, it is the variability that occurs in yield and in the quality of the oils when they are extracted from fresh or dried leaves. Therefore, it was proposed to use salicylic acid to optimize O. gratissimum essential oil production, to characterize physiological and biochemical responses involved in this process; as well as characterize the essential oils extracted from fresh and dry leaves. The plants were divided into two conditions, control plants (with water spr ay) and treated plants (spraying 1mM of salicylic acid). Extractions of essential oils from fresh and dried leaves were carried out 10 days after elicitation. It was also performed physiological and biochemical analysis within 10 days after the application of the elicitor. As expected, the elicitation of plants with salicylic acid promoted an increase in the yield of O. gratissimum essential oil. The highest yield was observed for fresh leaves. It was observed a content of 89.42% in fresh leaves and 75.72% in dry leaves of the major compound eugenol. In addition, an increase in the signaling defense responses was observed in elicited plants, such as the increase of antioxidant enzymes and Phenylalanine Ammonia Liase, and the content of hydrogen peroxide and lipid peroxidation. For growth variables were not observed differences between the conditions. For the quantification of micro and macromolecules treated plants showed lower protein content than control plants. It was concluded that the elicitation with salicylic acid optimized the production of essential oils in O. gratissimum, due to the process of defense signaling in plants. In addition, a higher yield of essential oil and the major compound, eugenol, was obtained from fresh leaf extraction.